Correlation of thoracic CT scan on reverse transcription-polymerase chain reaction in COVID-19 patients with end-stage renal disease - Dewanti, Sisilia; Tjempakasari, Artaria; Mardiana, Nunuk; Hayati, Fierly (Journal of Neonatal Surgery, 2025)
Background: Patients with end-stage renal disease (ESRD) regularly undergo hemodialysis and exhibit symptoms similar to those of COVID-19 infection. Therefore, it is necessary to carry out further exams, such as thoracic CT scans, using the COVID-19 Reporting and Data System (CO-RADS). The study aimed to analyze the correlation between thoracic CT scan imaging and reverse transcription-polymerase chain reaction (RT-PCR) in COVID-19 patients with ESRD. Methods: This study employed a cross-sectional study design with total sampling. Participants in this study were patients with ESRD who underwent regular dialysis. The data were collected from March 2020-2021. The collected data included COVID-19 diagnosis with RT-PCR and radiographic imaging based on CO-RADS. The statistical tests consisted of chi-square and Spearman correlation with p <0.05. Results: The findings from the chest x-rays of the participants revealed that 3.2% had no abnormalities, unilateral abnormalities of 14.3%, and bilateral abnormalities of 82.5%. Most participants had a CO-RADS 1-3 score of 63.5% and a negative RT-PCR of 63.5%. The study revealed that 82.5% of participants exhibited CO-RADS 1-3 and RT-PCR negative results, while 69.6% of participants showed CO-RADS 4-5 and positive RT-PCR (r = 0.462; p <0.001). Conclusion: A significant correlation exists between CO-RADS and RT-PCR in patients with ESRD